Sesame cake protein hydrolysis by alcalase: Effects of process parameters on hydrolysis, solubilisation, and enzyme inactivation - Demirhan, Elcin; Apar, Dilek Kilic; Ozbek, Belma (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2011)
We investigated the effects of process parameters (substrate concentration, enzyme concentration, temperature and pH) on the hydrolysis and solubilization of sesame cake protein as well as enzyme stability. The sesame cake protein was hydrolyzed by Alcalase enzyme (a bacterial protease produced by a selected strain of Bacillus Licheniformis) that was chosen among five commercial enzymes examined. The optimum process conditions for hydrolysis and solubilization were obtained as 15 g L-1 substrate concentration, 3 ml L-1 enzyme concentration, 50 degrees C and pH 8.5. Under these conditions, the values of degree of hydrolysis and solubilization were found as 26.3% and 82.1%, respectively, and enzyme lost its activity by approx. 56% at the end of 120 min processing time. Modeling studies were performed to determine the kinetics of hydrolysis, solubilization and enzyme inactivation. The relationship between hydrolysis and solubilization was found linear for all experimental conditions examined. The inactivation energy of Alcalase at the temperature range of 45-55 degrees C was determined to be 25544 J mol(-1).
Keywords: Sesame Cake Protein; Alcalase; Hydrolysis; Solubilization; Modelling; FUNCTIONAL-PROPERTIES; WHEY PROTEINS; CORN GLUTEN; KINETIC-MODEL; MECHANISM; INDICUM; Chemistry; Engineering